Decreased Indian hedgehog signaling activates autophagy in endometriosis and adenomyosis. Issue 2 (February 2021) - Zhou, Yingying; Peng, Yangying; Xia, Qingqing; Yan, Dewen; Zhang, Huiping; Zhang, Lingmin; Chen, Ying; Zhao, Xiumin; Li, Jie
Abstract : Indian hedgehog (Ihh) signaling regulates endometrial receptivity and is an indispensable mediator of embryonic implantation. Hedgehog signaling is known to regulate autophagy, and aberrant regulation of autophagy is critically implicated in the pathogenesis of endometriosis and adenomyosis. However, potential dysregulation of Ihh signaling and its role in autophagy modulation in these diseases remain obscure. In this study, we found that components of Ihh signaling were significantly decreased, whereas the autophagy marker protein, LC3BII, was significantly increased in endometrial tissues of women with endometriosis or adenomyosis. Inhibition of Ihh signaling with the small-molecule inhibitor GANT61 or Gli1 silencing in primary endometrial stromal cells increased autophagic activity, as measured by LC3 turnover assay and tandem mCherry-eGFP-LC3B fluorescence microscopy. Furthermore, we observed that GANT61 treatment significantly attenuated hydrogen peroxide-induced cell death, whereas disruption of autophagy with chloroquine diminished this effect. Collectively, these findings reveal that Ihh signaling is suppressed in endometrial tissues of patients with endometriosis or adenomyosis. This abnormal decrease may contribute to endometrial autophagy activation, which may promote aberrant survival of endometrial cells in ectopic sites in these two gynecological diseases.